FRI0730-HPR The concept of patient centered care in spondyloarthritis based on a multidisciplinary model. (12th June 2018) - Santos-Moreno, P.; Villarreal, L.; Buitrago-Garcia, D.; Cabrera, M.
Abstract : Background: Spondyloarthritis (SpA) is one the most prevalent musculoskeletal disease in the Americas, with an estimated prevalence of 0.5%. This group of patients presents a number of unmet needs for accessibility to the consultation, diagnosis and adequate treatments. That for this reason it is necessary to develop a program of Centers of Excellence (CoE), which allows answer to these needs and at the same time to add values for our health systems. Objectives: The aim was to create a program with pilot SpA centers initially in some countries that operate under the scheme of CoE, as they are already delineated in projects like REAL-PANLAR for rheumatoid arthritis. In a second phase and under the auspices of PANLAR (Panamerican league of associations for rheumatology) create a Pan American Network of Centers of Excellence in SpA (CESPA). Methods: We performed a systematic review of the literature in global and regional databases (Pubmed, Medline, Scopus, Lilacs), in order to search information on this research question-hypothesis. Subsequently and under a Delphi-modified methodology and consensus of involved rheumatologists lay the conceptual bases on this particular subject – the Centers of Excellence in SpA (CESPA). As a result of the above was defined as should be a CESPA. Results: In accordance with the principles of creation and operation of the CoE in particular, specific themes were developed by a coordinator who, after a review of the literature, presented a specific proposal on every particular topic that was discussed and then voted on and implemented swithin the CESPA concepts. A CESPA must have: 1. Screening Clinic and Early Diagnosis of SpA: the purpose is to rule out false positives of disease and to diagnose early SpA; 2. Model of patient-centered care: a model of frequencies of care should be implemented for SpA patients from the perspective of the different specialties involved in the multidisciplinary team; 3. Laboratories and images: conventional laboratory tests as having a minimum of 3–4 times a year and each patient will have conventional X-ray images of cervical and lumbosacral column at the beginning and then once a year. Ultrasound of entheses: upon admission to the program and then with a certain periodicity (annual) or depending of sensitivity to change (OMERACT). The same applies to the subject of MRI of sacroiliac joints and column for both diagnosis and follow-up; 4. Clinical guideline on SpA should be adapted and customized to the particular realities of some of our countries; 5. There must be a management (disease management) program that must include Structure, Process and Result Indicators to define CESPA as Standard, Optimal and Model; 6. There must be standardized education and research programs for patients and physicians at the center Conclusions: There is a global need to develop CESPAs, in order to define treatment targets type T2T-SpA, which would improve clinical outcomes and avoid so much disability and health economic costs. References: 1. Santos-Moreno P, et al. REAL-PANLAR Project for the Implementation and Accreditation of Centers of Excellence in RA Throughout Latin America. J Clin Rheumatol2015Jun;21(4):175–80. 2. Santos-Moreno P, et al. From the model of integral attention to the creation of centers of excellence in RA. Clin Rheumatol. 2015Mar;34(Suppl 1):S71–7. Disclosure of Interest: None declared